PERLINDUNGAN KONSUMEN TERHADAP PEMAKAI SKINCARE “STARLITE” YANG BEREDAR DIMASYARAKAT TANPA IZIN EDAR DARI BPOM DALAM PERSPEKTIF UNDANG-UNDANG NO.8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN: kasus produk starlite - nur mala (CV Rewang Rencang, 2025)
Various skincare products that do not have a distribution permit from the Food and Drug Supervisory Agency (BPOM), this study aims to analyze the role and effectiveness of the POM Agency in supervising and taking action against the circulation of skincare products and describing the legal protection situation for consumers. This study uses an approach that is an empirical juridical method, with primary data collection carried out through interviews with consumers and business actors. This study concludes that even though regulations related to Law No. 8 of 1999 have been enacted, there are still many obstacles and challenges in the field.